CLIMATE INVESTMENT IN PROVINCE PERSPEKTIF ACT NUMBER 25 YEAR 2007 - Sofiana, Ulya (Jurnal IUS, 2014)
Climate Investment In Province Perspective Act No. 25 Year 2007. Investment is important to improve economic of a country. Today, receiving foreign capital no longer consider the entry of foreign capital as a threat, or seen as, suspect, now developing countries argue that foreign capital can provide stock, bring managerial expertise, knowledge, capital and market connections. Issues to be studied in this paper is what should be considered by the state and the region to make investors interested in investing. The approach used in obtaining the data is normative juridical approach, which analyzes the roles of investment regulations relating to matters affecting the development of the investment climate. Investment climate needed to make investors willing to invest in economic activity in a country and region, meaning that the investment climate that raises investor confidence in the capital to be invested in certain businesses will benefit in the future. Investments generally require substantial funds and effect company in the long term, so investors are cautious to invest substantial funds if it is not profitable, therefore to support the creation of a favorable investment climate requires a study of the feasibility study on whether or not an investment project implemented and watched some good factors supporting and inhibiting factors such as regulatory policies regarding investment, rule of law, political stability, security, manpower, adequate facilities and so on.Key words : investment, investor, capital, province, economic, law, act